2003
DOI: 10.1017/s1357729800053315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of equi-molar dietary betaine and choline addition on performance, carcass quality and physiological parameters of pigs

Abstract: Betaine and its precursor choline were compared in their efficiency in affecting the performance, carcass traits, and liver betaine concentration of growing-finishing pigs. Individually penned Finnish Landrace and Yorkshire pigs and their crosses (30 kg; no. = 70) were offered the basal diet with no added betaine or choline, or the basal diet supplemented with low to moderate doses (250, 500 or 1000 mg/kg) of betaine (Betafin® S1), or with a similar molar amount of choline (578, 1155 or 2310 mg/kg of choline c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 22 publications
2
40
1
2
Order By: Relevance
“…These findings were unexpected as earlier studies, including those from our laboratory, have not previously demonstrated growth enhancement in animals fed a variety of experimental diets containing similar levels of betaine (Cadogan et al, 1993;Matthews et al, 1998;Overland et al, 1999;Matthews et al, 2001a,b;Fernandez-Fıgares et al,2 002;Lawrence et al, 2002). A new pig growth trial from Finland has recently been published reporting improved feed conversion ratios and daily gains with lower level of dietary betaine (Siljander-Rasi et al, 2003). In that study, the feed intake was restricted by a similar degree to that in the current report (80-85% of ad libitum).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These findings were unexpected as earlier studies, including those from our laboratory, have not previously demonstrated growth enhancement in animals fed a variety of experimental diets containing similar levels of betaine (Cadogan et al, 1993;Matthews et al, 1998;Overland et al, 1999;Matthews et al, 2001a,b;Fernandez-Fıgares et al,2 002;Lawrence et al, 2002). A new pig growth trial from Finland has recently been published reporting improved feed conversion ratios and daily gains with lower level of dietary betaine (Siljander-Rasi et al, 2003). In that study, the feed intake was restricted by a similar degree to that in the current report (80-85% of ad libitum).…”
Section: Discussionmentioning
confidence: 67%
“…The previously noted decrease in voluntary feed intake has been reported in betaine growth trials with females alone or with groups of mixed sexes (Matthews et al, 1998(Matthews et al, , 2001a. The Finnish study used mixed genders (females and castrated males), but they did not report their data by gender (Siljander-Rasi et al, 2003).…”
Section: Discussionmentioning
confidence: 95%
“…Choline, a betaine precursor, is also essentially required for a number of physiological functions such as membrane synthesis or formation of acetylcholine. In addition, it can be assumed that choline oxidation may be a rate-limiting step in the synthesis of betaine, since the addition of choline to diets for pigs was not as efficient as the addition of dietary betaine (Siljander-Rasi et al 2003). Choline and methionine are both used as feed additives in livestock nutrition.…”
Section: Betaine As a Functional Substitute For Methionine And Cholinementioning
confidence: 99%
“…This process utilizes more SAM than all of the other physiological methyltransferases combined, accounting for about 75% of homocysteine formation (Mudd & Poole 1975). Thus, methyl group of betaine can be used in transmethylation reactions for synthesis of creatine and may reduce the requirement for other methyl group donors such as methionine and choline (Siljander-Rasi et al 2003).…”
Section: Introductionmentioning
confidence: 99%